Reactive Transport Modeling of Swelling Processes in Clay‐sulfate Rocks. Issue 9 (15th September 2018) - Schweizer, Daniel; Prommer, Henning; Blum, Philipp; Siade, Adam J.; Butscher, Christoph
Abstract: Swelling of clay‐sulfate rocks often causes large problems in geotechnical applications such as tunneling. The primary mechanism inducing the increase in rock volume is the chemical transformation of anhydrite to gypsum, which is triggered by the ingress of groundwater. In the present study, a novel conceptual and numerical modeling approach is developed that emphasizes the effect of groundwater flow in conjunction with the associated availability of water and changing geochemical conditions on the chemical transformation of anhydrite to gypsum. A reactive transport model was developed and hydraulic, reactive, and solute transport as well as mechanical model parameters were estimated through an inversion process, constrained by geodetic ground heave measurements from a study site in Staufen, Germany. The conceptual model of the swelling process was implemented numerically through a dual‐domain modeling approach, whereby the mobile domain accounts for solute transport along discontinuities, and the immobile reactive domain represents the matrix. A mass transfer process accounts for diffusive and/or capillary water transport into the matrix, where the rate‐limited transformation of anhydrite to gypsum takes place. The model calculates heave at the land surface depending on water inflow, the transformation of anhydrite into gypsum and the local stress conditions exerted by overburden pressure. The results show that the proposed reactive transport modeling approach is suitable to quantify the observed swelling‐induced heave at the study site with a plausible parameterization. The study also highlights that diffusion is a decisive factor for the effective rate of anhydrite dissolution and, therefore, the overall chemical transformation process. Key Points: A new modeling approach was developed to simulate hydrogeological and geochemical conditions in swelling clay‐sulfate rocks Employing a dual‐domain approach allows to mimic preferential transport in discontinuities while considering geochemical transformations in the matrix The model captured transient hydrogeological and geochemical conditions at a field study site, successfully reproducing the observed heave at the land surface, as determined by geodetic measurements